2010
DOI: 10.1371/journal.pone.0010993
|View full text |Cite
|
Sign up to set email alerts
|

An Antimicrobial Peptide Regulates Tumor-Associated Macrophage Trafficking via the Chemokine Receptor CCR2, a Model for Tumorigenesis

Abstract: BackgroundTumor-associated macrophages (TAMs) constitute a significant part of infiltrating inflammatory cells that are frequently correlated with progression and poor prognosis of a variety of cancers. Tumor cell-produced human β-defensin-3 (hBD-3) has been associated with TAM trafficking in oral cancer; however, its involvement in tumor-related inflammatory processes remains largely unknown.MethodologyThe relationship between hBD-3, monocyte chemoattractant protein-1 (MCP-1), TAMs, and CCR2 was examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 98 publications
(122 reference statements)
6
145
1
Order By: Relevance
“…To generate macrophages, purified CD14 + cells (purified by negative selection) were incubated with M-CSF for 7 days as previously described. 2 The cells became large and granular by flow cytometric analyses and produced high spontaneous levels of MDC (Fig. 3), consistent with their maturation into macrophages.…”
Section: Human Bd-3 Induces Chemokines In Monocytederived Macrophagessupporting
confidence: 60%
See 1 more Smart Citation
“…To generate macrophages, purified CD14 + cells (purified by negative selection) were incubated with M-CSF for 7 days as previously described. 2 The cells became large and granular by flow cytometric analyses and produced high spontaneous levels of MDC (Fig. 3), consistent with their maturation into macrophages.…”
Section: Human Bd-3 Induces Chemokines In Monocytederived Macrophagessupporting
confidence: 60%
“…This molecule mediates the killing of microbes, 1 chemotaxis of CCR2 + cells such as monocytes 2 and activation of antigen-presenting cells (monocytes and myeloid dendritic cells 3,4 ). These diverse functions indicate that hBD-3 could play an important role in both innate and adaptive defences.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that several b-defensins recruit monocytes and macrophages, which do not express CCR6 (4,5). Recent studies suggest CCR2 as the responsible receptor for CCR6-independent migration of leukocytes (6,7).…”
mentioning
confidence: 99%
“…(Bottazzi et al, 1983;Zachariae et al, 1990) Other chemokines these include : CCL3, CCL4, CCL5, CXCL12 (Balkwill, 2004;Konishi et al, 1996;Schioppa et al, 2003). Nonchemokine chemotactic factors are also important, for instance: urokinase plasminogen activator (uPa) (Zhang et al, 2011), M-CSF, TGF; fibroblast growth factor, FGF; vascular endothelial growth factor, VEGF) (Joyce and Pollard, 2009;Lin et al, 2002;Sica and Bronte, 2007) and antimicrobial peptides (-defensin-3, BD-3) (Jin et al, 2010). Many of these molecules correlate with TAMs infiltration in different types of tumor, while other (eg.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%
“…Many of these molecules correlate with TAMs infiltration in different types of tumor, while other (eg. uPa, BD-3) are specifically associated with certain types of cancer, prostate and gastric cancer respectively (Jin et al, 2010;Zhang et al, 2011).…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%